(untitled) (Homoeopathy for All, 2025)
India due to its biodiversity is rich in many forest and mineral resources which plays a significant role in enriching the Homoeopathic Materia Medica and its contribution to a development of an effective healing system but are often overlooked and are seldom used in our daily homoeopathic prescriptions. This piece of work focuses mainly on two closely related remedies one from plant kingdom (Azadirachta indica) and another from mineral kingdom (Sulphur) along with their identification, basic information about the drugs.